DCNMAF: Dilated Convolution Neural Network Model with Mixed Activation Functions for Image De-Noising - C. Radhiya Devi, S. K. Jayanthi (International Journal of Intelligent Systems and Applications in Engineering, 2023)
In image processing applications pre-processing the image is the most crucial step. It is essential to eliminate the noise of the image and enhance its quality for further processing. This paper proposes a novel idea to de-noise the image using the Dilated Convolution Neural Network model with Mixed Activation Functions (DCNMAF). Performance Evaluation is done based on the metrics PSNR and SSIM and the proposed model out performs other methods with higher PSNR and SSIM values.